2015
DOI: 10.1542/peds.2014-0895
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation Strategies for Early Treatment of RDS in Preterm Infants: An RCT

Abstract: BACKGROUND AND OBJECTIVES: There is evidence that new methods of noninvasive ventilation (NIV) support have significantly changed respiratory distress syndrome (RDS) management in preterm infants. Further perspectives for neonatologists involve the assessment of different NIV strategies in terms of availability, effectiveness, and failure. This study evaluates the efficacy of 2 different NIV strategies for RDS treatment in very low birth weight (VLBW) infants: nasal synchronized intermittent positive pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Most of the evidence that contributed to this comparison was indirect and there was only a single RCT that had compared these two interventions. 57 Millar et al 75 High quality-very confident that the true effect lies close to that of the estimate of the effect. Moderate quality-moderately confident in the effect estimate: the true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most of the evidence that contributed to this comparison was indirect and there was only a single RCT that had compared these two interventions. 57 Millar et al 75 High quality-very confident that the true effect lies close to that of the estimate of the effect. Moderate quality-moderately confident in the effect estimate: the true effect is likely to be close to the estimate of the effect, but there is a possibility that it is substantially different.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, 13 studies 25,28,30,32,33,37,[40][41][42][43][44]51,57 were regarded as having a low risk of bias, the remaining studies were found to have variable degrees of risk of bias. Fourteen studies had high risk of bias 27,[34][35][36]38,45,[47][48][49][50]52,[54][55][56] with issues in randomisation and/or allocation concealment.…”
Section: Risk Of Bias Assessment Of Included Studiesmentioning
confidence: 99%
“…Advances in neonatal intensive care and mechanical ventilation of newborns have increased infants’ survival during recent years and was subject of many recent investigations ( Donn et al, 2003 ; Wu et al, 2015 ; Armanian et al, 2014 ; Salvo et al, 2015 ; Chu et al, 2015 ; Akinloye et al, 2014 ; Schmölzer et al, 2014 ). New ventilation methods and techniques that have newly become available have made the mechanical ventilation in neonates a masterpiece in the twenty-first century ( Keszler, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the effects of some modes of ventilation in the treatment of RDS in prematurity, such as BiPAP vs nasal synchronized intermittent positive pressure ventilation (NSIPPV) 9 ; nasal bi-level PAP (N-BiPAP) vs sigh-PAP (n-SiPAP) 10 ; and nasal intermittent positive pressure ventilation (NIPPV) vs nasal continuous positive airway pressure (NCPAP) 11 . This is the first report to compare normal-frequencyassisted ventilation for preterm infants ([?]…”
Section: Discussionmentioning
confidence: 99%